Ionic Liquid-Based Electrolytes for Supercapacitor and Supercapattery - Yu, Linpo; Chen, George Z. (Frontiers in Chemistry, 2019)
There is a strong desire to replace or complement aqueous and organic electrolytes by ionic liquids (ILs) in electrochemical energy storage (EES) devices to achieve high operating voltages and hence high energy capacity. ILs are regarded as the inherent and competitive electrolytes since they were introduced to the electrochemical research community, because they can overcome many disadvantages of the conventional aqueous and organic electrolytes, such as narrow potential windows, volatility and flammability. This paper reviews critically the recent literatures on IL-based electrolytes used in supercapacitor and supercapattery which is a generic term for various hybrid devices combining the merits of rechargeable battery and supercapacitor and often shows capacitive behaviour. Fundamentals of supercapattery will be briefly explained with typical examples. From the respective of IL-based electrolytes, the current progresses of neat IL, IL-mixture, and IL-based solid electrolytes used in supercapacitor and supercapattery will be introduced in sequence, followed by a discussion on the prospects of innovations that IL-based electrolytes will bring about in the future development of supercapacitor and supercapattery.